2013
DOI: 10.1007/s13278-013-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

Good location, terrible food: detecting feature sentiment in user-generated reviews

Abstract: A growing corpus of online informal reviews is generated every day by non-experts, on social networks and blogs, about an unlimited range of products and services. Users do not only express holistic opinions, but often focus on specific features of their interest. The automatic understanding of "what people think" at the feature level can greatly support decision making, both for consumers and producers. In this paper, we present an approach to feature-level sentiment detection that integrates natural language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Wang et al () performed text mining on geotagged tweets in the response to a wildfire and detected the attitudes of people, such as their appreciation to fire fighters. Looking into TripAdvisor hotel reviews, Cataldi et al () proposed an approach for detecting the sentiments of people toward different aspects of a hotel, such as its location convenience and food quality. Wang and Zhou () performed sentiment analysis on TripAdvisor hotel reviews within the same city and found that spatial dependence exists in the satisfaction of customers.…”
Section: Knowledge Discovery From Geo‐text Data and Data‐driven Geospmentioning
confidence: 99%
“…Wang et al () performed text mining on geotagged tweets in the response to a wildfire and detected the attitudes of people, such as their appreciation to fire fighters. Looking into TripAdvisor hotel reviews, Cataldi et al () proposed an approach for detecting the sentiments of people toward different aspects of a hotel, such as its location convenience and food quality. Wang and Zhou () performed sentiment analysis on TripAdvisor hotel reviews within the same city and found that spatial dependence exists in the satisfaction of customers.…”
Section: Knowledge Discovery From Geo‐text Data and Data‐driven Geospmentioning
confidence: 99%
“…Bosch et al have developed a system that conducts real-time filtering in order to acquire the contents that appeal to the customer out of the share clusters the user is exposed to [10]. Based on the shares that are made, Cataldi et al have tried to make inferences about the issues on agenda [11]. On the other hand, Kang et al sought to determine the connection between the events in addition to the event inferences [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This strand of natural language processing aims at the classification of a textual document into a subjective category (e.g., good/bad) or along a single continuous dimension from negative to positive [12]. Domain-specific sentiment analysis techniques have been tailored to online reviews of hotels and travel destinations, adopting syntactic parsing [5], as well as supervised machine learning approaches [20]. Opinions can be explicit or implicit in a text, the latter being especially difficult to extract from simple methods based on syntactic matching.…”
Section: Related Workmentioning
confidence: 99%
“…The measurement of public sentiment about a given topic in such outlets has already tangible applications in politics, marketing, and business analytics [10]. However, existing techniques aim at quantifying sentiment on a negative-positive spectrum, ignoring more nuanced aspects of emotions [5]. While some research has targeted this corpus from a geographic perspective [14,1], no attempt has been made to explore places with respect to their emotional structure.…”
Section: Introductionmentioning
confidence: 99%